Comparison of equivalent earthquake load method for TEC-2007 and TBEC-2018: Adıyaman province example - Yetkın, Musa; Taş, Ömer Faruk; Sayın, Erkut (My University, 2023)
In this study, in terms of their approach to the equivalent earthquake load method, a comparison of the Turkish building earthquake codes published in 2007 and 2018 was made. For the study a reinforced concrete residential building, which is thought to be designed for the Adiyaman provincial center and its other districts was selected. It is assumed that the residential building has three spanning in the x and y directions (in plane) and the structural system consists of columns-beams. The floor height of the building was taken as 3 m for each floor and the number of floor was chosen as six, considering the construction style of Adıyaman province. The first natural vibration period of the residential building was determined with the help of the Rayleigh ratio formula and the empirical approach. Then, according to both earthquake codes, the base shear forces were determined separately for different soil classes using the structural characteristics of the residential building. Firstly, each code was evaluated within itself, and then a comparison of the codes with each other was made.
Keywords: TBEC-2018; Base shear force; Equivalent earthquake load method; TEC-2007